Comparison of fit among different types of post restorations luted with conventional cement - Al-Mustwfi, Ehsaan S; Al-Azzawi, Haitham J (Journal of Baghdad College of Dentistry, 2013)
Background: with the advent of new postmaterial in dentistry, it has become important to measure fitness of post restoration along the horizontal plane of the root space.This study aimed to measure and compare, the cement film thickness of conventional zinc phosphate cement in micrometer between the post and root dentin along horizontal plane at different post space regions (coronal, middle and apical) of four types of posts, by using stereomicroscopy. Material and methods: Thirty-two extracted human maxillary canines, mandibular canines and maxillary central incisors (n=32) were instrumented with ProTaper system files (hand use) and obturated with gutta-percha for ProTaper and AH26® root canal sealer. After 24hrs of incubation at 37ºC, post space was prepared using FRC Postec® plus drills no.3 and ER Cera reamer size 70, creating 10 mm deep post space. The prepared samples were then randomly divided into four main groups (8 samples each) according to the type of post used (Group A: fabricated cast metal post), (Group B: fabricated zirconia post), (Group C: prefabricated glass fiber reinforced composite post), (Group D: prefabricated zirconia post). After cementation and incubation period of 24hrs, each root was sectioned horizontally into 3 discs (2mm in thickness) at the coronal, middle and apical regions of the root space. The cement thickness between post and root dentine was measured (in µm) by using a stereomicroscope. Results: The results of this study showed that the lowest mean of cement thickness was in group C (35.28?m), followed by group A (78.12?m) and group D (81.9?m), and all three groups demonstrated acceptable cement thickness, while group B produced unacceptable cement thickness (127.34?m). One way ANOVA test revealed a statistically highly significant difference for the cement thickness among four post types used within each region of the root. Conclusions: the root region and type of post system have an effect on cement thickness along post space.